The Importance of Disability Training for Health Professionals in Santiago de Cali - Peña Hernández, Paula Andrea; Celorio Montaño, Johanna (Rastros Rostros, 2014)
This article seeks to describe the educational needs and expectations of some health professionals inthe city of Santiago de Cali in the area of post-graduate disability training. An exploratory study wasconducted with information collected in two higher education institutions in the city of Cali usingan instrument designed by the researchers that incorporated socio-demographic, academic, laborand needs, and educational expectation variables. Of those surveyed, 48% claimed to be interested indisability training. Reasons for undertaking post-graduate studies included job-related subject matter,and the opportunity for better pay. Many people are interested in acquiring disability training, however,no such programs are offered in Cali
Keywords: education; professional groups; people with disability; post-graduate